PERLINDUNGAN ANAK SEBAGAI KORBAN KEKERASAN SEKSUAL MELALUI PENEGAKAN HUKUM DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Raudatul Mardiyah Sahran; Nur‘ayiyin; Nur Alfin Hadi; Feni Puspitasari (Universitas Islam Indragiri, 2025)
The prosecution of sexual crimes against children in Indonesia is regulated by various laws and regulations, one of which is Government Regulation in Lieu of Law (Perppu) Number 1 of 2016. This Perppu was later enacted as Law Number 17 of 2016 as the second amendment to the Child Protection Law Number 23 of 2002. The regulation was introduced in response to the increasing number of sexual violence cases against children and the inadequacy of the previous legal system in providing a sufficient deterrent effect to offenders. Research using normative-empirical methods shows that the increased severity of punishments, including the introduction of additional penalties such as chemical castration, aims to strengthen child protection and reduce the incidence of sexual crimes. However, the effectiveness of these harsh penalties is still debated because they have not fully prevented sexual offenses comprehensively. This is due to social and psychological factors, as well as weak environmental supervision. The revised Child Protection Law emphasizes that the best interests of the child must be the main priority. Therefore, efforts to address sexual violence against children must be carried out holistically, not only through severe criminal sanctions but also through education, prevention, victim rehabilitation, and strengthening the role of families and communities.